Verrucosispora sp. K2-04, potential xylanase producer from Kuantan Mangrove Forest sediment - Mohd Omar, Suhaila; Mohd Farouk, Norsyafawati; Abdul Malek, Nurfathiah; Zainal Abidin, Zaima Azira (2017)
Abstract: Xylanase is the key enzyme that involve in the hydrolysis of xylan, the main constituent of the complex hemicellulose of the plant cell wall. In this study, forty actinomycetes that were isolated from sediment of Kuantan Mangrove Forest, Malaysia, were tested for their ability to produce extracellular xylanase. At least 15 isolates were able to degrade xylan in the primary agar-based screening using marine agar containing 0.1% (v/v) azo-xylan (Birchwood). The degradation of xylan was indicated by the formation of halo zone around the colonies and the clear zone index (CZI) was calculated as a ratio of the clearing zones to the colony size. Isolate K2-04 with CZI 3.35 ± 1.91 was identified through 16S rRNA study as Verrucosispora sp. This isolate was further grown in marine broth and incubated at 30 °C, 200 rpm for 20 days. The growth of K2-04 and the xylanase activity was measured at day 2, 4, 6, 12 and 18 respectively. The highest enzyme activity for the crude enzyme was recorded at day 18 (1.836 U/mL) and exhibited stability after 20 days storage at 4°C. This study serves as a preliminary study to characterize the properties of Verrucosispora sp. K2-04, rare actinomycete of Kuantan Mangrove Forest, Malaysia.